Sharing Knowledge Produk Halal dan Pelatihan Pendamping PPPH UMKM di Desa Sumbersekar, Kecamatan Dau, Kabupaten Malang - Zuraidah Zuraidah; Ni'matuz Zuhro; Mardiana Mardiana (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2024)
MSME, from the beginning to the end recognized as businesses, always tries to get information for the recognition of the business. But in fact, in the middle of the way, the spirit of business is broken by the government regulation procedures which lead to updates every year. We, as researchers and practitioners, have to initiate in helping business actors or MSMEs in providing socialization to mentoring. Especially in the government activities in 2022, BPJPH targeted 30 thousand halal-certified products. By targeting Indonesia as the center of the halal industry, SMEs and MSMEs must get a halal certificate first through the PPH assistance program with the Business Actor Statement scheme or known as Self Declare. This service took place in Sumbersekar Village, Dau District, Malang Regency with a focus on MSMEs in sharing knowledge and PPH assistance by using this Participatory Action Research, this service passes four stages, namely: planning, doing action, observing, and reflecting. The implementation was done in some action stages by using PAR method as follows: MSMEs mentoring in Sumbersekar Village got some changes: first, MSMEs are able to identify problems, such as not having PIRT, NIB, and brand; second, they enhance the understanding that entrepreneurship should be started as the foundation of the government regulations to build the economic independence; third, they are able to do activities in line with the PPH knowledge sharing to mentoring. The results of the service were obtained from 23 MSMEs that were recorded and 15 MSMEs managed to obtain a Business License and obtain Halal Certification, while the remaining 8 MSMEs were still constrained by the licensing process because they were still making product brands. These 8 MSMEs, of course, still get service assistance until they get the expected license letter.